Transmission of SARS-CoV-2 variant B.1.1.7 among vaccinated health care workers. Issue 11 (2nd November 2021) - Ioannou, Petros; Karakonstantis, Stamatis; Astrinaki, Eirini; Saplamidou, Stamatina; Vitsaxaki, Efsevia; Hamilos, Georgios; Sourvinos, George; Kofteridis, Diamantis P.
Abstract: Background: Vaccination against COVID-19 is among the most effective measures to stop the spread of the disease. However, acceptance of vaccination against COVID-19 among HCWs has not been universal and emergence of new variants with increased transmissibility, reduced neutralization by BNT162b2 vaccine-elicited sera and ability to cause breakthrough infections in vaccinated individuals is concerning. The aim of this study was to compare viral load, clinical presentation at diagnosis and type of exposure among vaccinated (with BNT162b2) and non-vaccinated healthcare workers (HCWs). Methods: Prospective cohort of HWCs diagnosed with COVID-19 by nasopharyngeal PCR from 4 January to 14 April. Viral loads were expressed by the cycle threshold (Ct) in PCR. Results: During the study period 55 HCWs were found positive for SARS-CoV-2, most of whom (44/55) were identified from March 28 to April 14 during an in-hospital COVID-19 outbreak. Of the 55 HCWs, 21 were fully vaccinated and another three had received one dose. Most cases (54/55) were due to variant B.1.1.7. Vaccinated and unvaccinated HCWs did not differ significantly in regards to age, gender, site of acquisition, presence of symptoms at diagnosis and viral load. Conclusions: This study found a similar viral load in vaccinated and non-vaccinated HCWs infected by SARS-CoV-2 variant B.1.1.7, suggesting potentially reduced efficacy of BNT162b2 in preventing transmission of B.1.1.7.